CONFLICT AS A WAY OF BEING OF POLITICS. MACHIAVELLIAN CONTRIBUTION TO THINK THE POWER - Ignacio Luis Moretti (Astrolabio: Nueva Época, 2015)
The conceptual challenge of thinking politics refers to the attempt - always, by definition, precarious, fragile and destined to failure- to grasp an intrinsically polysemic object and action defies straitjacket or limitation.  This article will propose a deliberate code reading; a specific interpretive framework for thinking about politics; understanding the conflict as its hopelessly constitutive category. With this purpose, we will consider the work of Nicholas Machiavelli enjoying fertility to think this troubled specificity of the political. The methodological approach was purely theoretical, through an exercise of exegesis of texts Machiavellian and enhancement of its contemporary political thinking.